Diagnóstico socioeconómico ambiental del sitio Shiquil del Cantón Chilla, buscando el mejoramiento de las condiciones de vida de la población - Aragundi Orellana, Manuel Patricio (2016)
The integrating project is carried out in the Shiquil site belonging to the Chilla Canton of the Province of El Oro, in which one of the main problems that exists there is identified, for which technical visits to the place of study have been made. Carried out interviews with the residents of the sector who stated that the main problem of the sector is the lack of water resources in times of drought that begin in the months of August to December, months in which they can not plant their products Short cycle. It is for this reason that the objective is to implement an artificial reservoir in the site to supply water resources in the sector so that they can plant and have a safe harvest. Also in the place of study it was verified through direct observation that the introduction of exotic species such as pine, which has caused the alteration of the ecosystem and its landscaping beauty, thus affecting crops grown in Shiquil , Scarifying the vital resource for the proper development of the same. Although this resource is vital for the flora and fauna corresponding, it is also for the human being, due to the use of it to meet their needs, Which has made it an important aspect in the economy of the people, since it has been used in the different productive economic activities that have been developing over time mainly in agriculture. The scarcity of water resources for agriculture causes the inhabitants to engage in other activities, whether they migrate to other cities for lack of work or are engaged in construction, livestock, fishing, indiscriminate hunting, With the implementation of the reservoir will be supplied with water resources so that the farmers increase their gloom and generate employment avoiding that the inhabitants migrate to other sites and remain to produce their lands. The water resource is vital for human life, flora and fauna, it is there that falls the importance of this project that will benefit the inhabitants of the Shiquil sector ..